Two new species of Melanoplus Stål, 1873 (Orthoptera: Acrididae: Melanoplinae) from northeastern Mexico - Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Horta-Vega, Jorge V. (Zootaxa, 2013)
Two new species of the genus Melanoplus Stål 1873 are described. M. trachodes n. sp., and M. parvus n. sp., both of which are endemic to the cool-temperate mountains of the Eastern Sierra Madre (ESM) in northeastern Mexico. Their habitat represents a transition zone between the ESM and the semiarid High Plateau Biogeographic provinces. This transition zone is characterized by an elevation range from 1,900 to 3,400 m and unique ecological conditions, which give rise to a considerable number of endemisms.